Evaluation of M-Score and ICOFR on PT X - Galuh Riawati; Ancella Anitawati Hermawan (E-Jurnal Akuntansi, 2024)
In 2023, the Ministry ABC suspects that there has been manipulation of the financial statements of PT X, with reporting profits for years but negative cash flow, failure to pay so that it was sued for bankruptcy. The research aims to analyze indications of manipulation of financial statements and internal control over financial reports (ICOFR) at PT X. The research uses secondary data in the form of company annual reports from 2012-2022. Indications of financial report manipulation are obtained from the Beneish M-Score calculation. ICOFR analysis is carried out by scoring using the manual content method of 90 ICOFR A Compendium of Approaches and Examples indicators. The research results show that there are indications of manipulation of financial reports except in 2020 and 2021 and internal control over financial reports is getting better from year to year. Good ICOFR score does not guarantee that financial reports are free from indications of manipulation.